FILOZOFIJA MEĐUNARODNOG OBIČAJNOG PRAVA: DOVOLJNA JE PRAKSA - Hrnjaz, Miloš (Pravni zapisi, 2021)
The main objective of this paper is to critically assess the dominant additive theory of the formation of Customary International Law by using the concept of discursive normative practice and the work of Gerald Postema. My central conclusion is that the use of this concept provides an explanation of the process of formation of Customary International Law that is superior to the additive theory which consists of two elements – practice and opinio juris. On theother hand, Postema’s theory also has its own weaknesses, and this paper explores ways to improve it.
Keywords: International Law; Customary International Law; International Court of Justice; sources of international law; discursive normative practice